1998
DOI: 10.1144/gsl.sp.1998.130.01.08
|View full text |Cite
|
Sign up to set email alerts
|

A geophysical investigation of saline intrusion and geological structure beneath areas of tidal coastal wetland at Langstone Harbour, Hampshire, UK

Abstract: Experiments are described that test how tide and geological structure affect saline intrusion beneath an area of coastal wetland in Hampshire, southern England. Resistivity tomography and time-dependent ground conductivity surveys were carried out at two closely located survey sites. Resultant maps and sections show clear geophysical anomalies that can be attributed to tidal saline intrusion and to the position of geological structures. Results suggest that migration of saline groundwater is, in places, out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Monitoring of borehole water levels and hydrochemistry often fails to predict the timing of SI, particularly in heterogeneous aquifers, where seawater may be transported along a small number of preferential flow paths. Time‐lapse resistivity and electromagnetic surveys have been used in various studies to investigate SI (e.g., Comte & Banton, ; Fitterman, ; McDonald et al, ), although these typically require a large footprint for the long‐term installation of monitoring apparatus or repeated surveys during the predicted period of SI risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring of borehole water levels and hydrochemistry often fails to predict the timing of SI, particularly in heterogeneous aquifers, where seawater may be transported along a small number of preferential flow paths. Time‐lapse resistivity and electromagnetic surveys have been used in various studies to investigate SI (e.g., Comte & Banton, ; Fitterman, ; McDonald et al, ), although these typically require a large footprint for the long‐term installation of monitoring apparatus or repeated surveys during the predicted period of SI risk.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring of borehole water levels and hydrochemistry often fails to predict the timing of SI, particularly in heterogeneous aquifers, where seawater may be transported along a small number of preferential flow paths. Time-lapse resistivity and electromagnetic surveys have been used in various studies to investigate SI (e.g., Comte & Banton, 2007;Fitterman, 2014;McDonald et al, 1998), although these typically require a large footprint for the long-term installation of monitoring apparatus or repeated surveys during the predicted period of SI risk. This paper explores whether borehole measurements of self-potential (SP) may represent an alternative means of identifying a nearby saline front, as concentration gradients are known to generate SP, through the development of an electrochemical exclusion-diffusion potential V EED (e.g., Jackson, 2015;Jouniaux et al, 2009;Lanteri et al, 2009;Leinov & Jackson, 2014;Martínez-Pagán et al, 2010;Revil, 1999;Westermann-Clark & Christoforou, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Typical ranges of geophysical properties such as electrical resistivity for unconsolidated and consolidated materials together with their varying pore water types are given in a number of standard texts [see Table after Telford et al () and Reynolds ()]. Of particular importance to working in the transition zone, as we have already noted, is the large influence that saline saturation has on the relative resistivity of different materials (McDonald et al , ) where up to four‐orders of magnitude difference can be seen between salt‐saturated sand and dry sand. The empirical relationship presented by Archie () demonstrates that bulk resistivity (or its inverse bulk conductivity) is related to pore fluid conductivity, porosity and degree of saturation where a material contains little or no clay.…”
Section: The Geophysical Modelmentioning
confidence: 82%
“…In the two studies reported here, it is the relative contrasts in conductivity (or resistivity) that are shown to be important for discrimination of subsurface geology and thus palaeogeographic reconstruction. McDonald et al () clearly demonstrated the influence of geology, and in particular the effect of porosity and permeability, on saltwater intrusion in a study of coastal wetland at Langstone Harbour, UK. Here a buried channel complex consisting of muds, sand, peats and gravels on an undulating chalk bedrock was investigated with ERT and FDEM.…”
Section: Geophysics In the Transition Zonementioning
confidence: 99%
“…Additional control is also required to distinguish between fluid conductivity contributions and those due to clay component litholologies (e.g., Gabriel et al 2003). Onshore ground electrical and electromagnetic geophysical measurements related to saline conditions at coastal and wetland locations in the UK were reported by Barker (1982Barker ( , 1990 and McDonald et al (1998). Ground geophysical investigations of the coastal zone of the Welsh mainland in the vicinity of Anglesey were reported by Obikoya and Bennell (2008).…”
Section: Geologymentioning
confidence: 99%